IMPLEMENTASI ASAS TATA KELOLA YANG BAIK PADA KOPERASI MITRA DHUAFA REGIONAL ACEH - Anggraini, Sarah; BZ, Fazli Syam; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to analyze how the principles of good governance apply to Aceh Regional Mitra Dhuafa Cooperative (KOMIDA) based on the policy standards that have been determined by the National Committee on Governance Policy (KNKG). The implementation of a standardized governance system in KNKG policies is able to encourage and improve management and evaluate how the activities and performance of the organization are in order to achieve efficiency and effectiveness from the functions and assets of the Aceh Regional Mitra Dhuafa Cooperative (KOMIDA).This research using descriptive analytical research to 20 employees of Aceh Regional Mitra Dhuafa Cooperative (KOMIDA). Data collection techniques used research instruments in the form of questionnaires and interviews. The results obtained from this study that Aceh Regional Dhuafa Mitra Cooperative (KOMIDA) has implemented an improved governance system based on the KNKG standard which is described as follows. The principle of transparency scored 86 percent in the very good category, the principle of accountability scored 84.25 percent in the very good category, the principle of accountability resulted in a score of 88.25 percent in the very good category, the principle of independence scored 84.5 percent in the very good category and the principle of fairness resulted in a score of 88.5 percent in the very good category.Keywords–Principles of Good Governance, Aceh Regional Mitra Dhuafa Cooperative (KOMIDA)